2018
DOI: 10.1186/s12891-018-2264-7
|View full text |Cite
|
Sign up to set email alerts
|

Infection after knee replacement: a qualitative study of impact of periprosthetic knee infection

Abstract: BackgroundApproximately 340,000 knee replacements are performed each year in the USA and UK. Around 1% of patients who have had knee replacement develop deep infection around the prosthesis: periprosthetic knee infection. Treatment often requires a combination of one or more major operations and antibiotic therapy. This study aimed to understand and characterise patients’ experiences of periprosthetic knee infection.MethodsQualitative semi-structured interviews were conducted with 16 patients (9 men, 7 women; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 44 publications
0
18
0
1
Order By: Relevance
“…3 Treatment of prosthetic joint infection is expensive and protracted, and both the infection and the treatment have profoundly negative effects on patients and their families. [4][5][6][7] Treatment options include antibiotic suppression, debridement and retention of implants, excisional arthroplasty, and one-stage or two-stage revision. 8,9 However, all of these treatment options are associated with substantial morbidity and a high risk of adverse outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…3 Treatment of prosthetic joint infection is expensive and protracted, and both the infection and the treatment have profoundly negative effects on patients and their families. [4][5][6][7] Treatment options include antibiotic suppression, debridement and retention of implants, excisional arthroplasty, and one-stage or two-stage revision. 8,9 However, all of these treatment options are associated with substantial morbidity and a high risk of adverse outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…It has the potential to improve patients' quality of life by reducing pain and improving function, but there is also potential for serious complications. Prosthetic joint infection (PJI) is a potentially life-threatening condition associated with severe pain, functional difficulties and poor quality of life [1][2][3]. If left untreated, PJI may result in limb amputation or death [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Surgical treatment can be prolonged sometimes involving multiple surgeries and hospitalisations and prolonged antibiotic treatment. PJI and its treatment has a profoundly negative impact on all aspects of patients' lives, including physical, social, emotional and economic aspects and patients undergoing treatment can experience feelings of isolation and insecurity, and an inability to live independently [1,2]. Cahill and colleagues found that the profoundly negative impact on patients' social functioning and mental health is notable with this group of patients rating their overall quality of life as poor with 12% of patients rating their current situation as equivalent to or worse than death [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even for patients whose devices are replaced, there could be significant negative impact on patient quality of life due to the infection and related treatment. Studies in other conditions have identified a significant impact of surgical site infection on patient quality of life . Further research is needed to understand the specific quality‐of‐life impact of SCS device‐related infections.…”
Section: Discussionmentioning
confidence: 99%